Priorisiation of genetic innovation product profiles for Uzbekistan, demand creation for newly released varieties and seed systems stakeholder workshop with NARES - CIP report - Andrade, Jorge; Mshvidobadze, Vakhtang (International Potato Center, 2023)
The meeting was organized by CIP and ICARDA to prioritise genetic innovation product profiles and demand creation for newly released varieties and to work out a participatory multistakeholder process for local seed businesses of less commercial crops. The meeting was held in a conference room with online participation by CIP and ICARDA representatives, who delivered the presentations for the participants and were actively engaged in the discussion. From the Uzbekistan side, the meeting was attended by representatives of different state and academic institutions and INGOs. Up to 30 people participated in the meeting. During the meeting, the simultaneous English-Russian-Uzbek translation was organised for all presentations, as well as for the discussion and Q&A sessions.